The Performance of the Dinas Sosial in Resolving the Poor at the Selayar Islands Regency - Muhammad Guntur; Iramaya Iramaya (Pinisi Journal of Social Science, 2022)
This study aims to determine how the performance of the Dinas Sosial in Handling the Poor at Selayar District by using the four performance indicators proposed by Dwiyanto (2008) namely Service Quality, Responsiveness, Responsibility, and Accountability. This research method is descriptive qualitative with the focus of research at the Dinas Social of Selayar District. Data collection techniques were carried out by interviews, observation and documentation. The results of the study, it can be seen that Dinas Sosial in Handling the Poor at the Selayar District carried out their duties well. This can be seen from the implementation of the four indicators of performance research, namely service quality, responsiveness, responsibility, and accountability. The results of this study indicate that the Performance of the Dinas Sosial in Handling the Poor at the Selayar District through the Family Hope Program (FHP) has been going well, marked by reduced the number of families who receive assistance each year.